Aplicación móvil de realidad aumentada en modelado 3d orientada al proceso enseñanza-aprendizaje de la anatomía humana - Zambrano Vera, Wilmer Orley (2021)
In this technical project, a mobile application of augmented reality in 3D modeling was developed to support the teaching-learning process of anatomy in the educational field. Where the specific objectives were established as methodological phases, the life cycle for this model consists of phase 1 App development, with 5 stages: determining the structure and content of the mobile app, designing the objects that will make up the 3D model, configuration and application of the selected AR tool, design and development of the application on the selected platform, write the required source code; and phase 2 App tests with 3 stages: unit tests, control flow tests with which errors were located and eliminated from the application and usability tests that were applied to a sample of 26 people made up of students and teachers, where it was established that the AR mobile application positively influences the learning of human anatomy. In addition, most of the participants gave a satisfactory global assessment in relation to the functionalities of the mobile app, with a reliability level of Cronbach's Alpha = 0.95.